Peningkatan Keterampilan Mengidentifikasi Unsur Cerita Melalui Model Cooperative Integrated Reading and Composition (CIRC) di Kelas V SDN Soko Kabupaten Tulungagung - Asngari, Muhammad Muhtar; Murti, Tri; Madyono, Suhel (Wahana Sekolah Dasar, 2019)
This study aims to describe the application and improvement of skills in identifying elements of the story through the CIRC model. This type of research used is Classroom Action Research. The subjects of the study were the fifth grade students of SDN Soko, which consisted of 21 students, consisting of 11 male students and 10 female students. Student activity in the first cycle reached 82%, increasing in the second cycle to 94%. The average value of students' skills in the first cycle was 73 with a 66% classical completeness and in the second cycle the average score was 78 with a 88% classical completeness. Penelitian ini bertujuan untuk mendeskripsikan penerapan dan peningkatan keterampilan mengidentifikasi unsur cerita melalui model CIRC. Jenis penelitian yang dipergunakan adalah Penelitian Tindakan Kelas (PTK). Subjek penelitian adalah siswa kelas V SDN Soko yang berjumlah 21 siswa, terdiri dari 11 siswa laki-laki dan 10 siswa perempuan. Aktivitas siswa pada siklus I mencapai 82% meningkat pada siklus II menjadi 94%. Nilai rata-rata keterampilan siswa pada siklus I sebesar 73 dengan ketuntasan klasikal 66% dan pada siklus II nilai rata-rata mencapai 78 dengan ketuntasan klasikal 88%.